Características epidemiológicas da esquistossomose mansoni em áreas endêmicas rural e urbana de Minas Gerais - Marcia Nogueira Amorim (1994)
A croos secctional survey was placed to analyse Schistosama mansani infection in two population of Minas Gerais state with distinct characteristics of urbanization. Prevalence and risk factors analysis depending on different number of stool examination was studied. ln rural area (302 inhabitants), the prevalence was 38,8%, geometric means 117,8 epg. and 2% hepatoesplenic form. Housekeeping was the activity responsible for most water contact and was more frequent betwen l0 and 29 years old. Only pre treatement and age were independenty associated with infection. In urban area (800 inhabitants), the prevalence was 9,7%, geometric means 62,4 epg and nobody had hepatoesplenic form. The most people reported water contact for leisure activites and aged betwen 15 and 29 years old. Independent variables associated with infection were: >= 10 years old, fishing and swiming, and living bad house. Prevalence was 8,7% and 14,5% using 1 and 3 stool examination, respectively. On the other hand the risk factors were not alterated by increasing the number of stool examination.